Estimation of Stature from head length in medical students. - Chandrakant M Kokatanur1 , Ajay V Patil2 , Vinay Bannur3 , Karan Deep Mishra4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Identification of an individual, living or dead is of paramount importance in forensic practice,especially when dismembered body parts or skeletal remains are received for examination. Estimation ofstature is one of the important criteria in terms to determine the identity of individual. Many studies haverevealed the relationship between stature and some parts of the skeleton and the body parts in consideration.This study will helpful when only skull is available for medico-legal examination. Aim: To estimate statureof person from head length. Material and Methods: A cross sectional study was conducted in KrishnaInstitute of Medical Sciences for a period of 2 months from April to May 2018. Data was collected bymeasuring stature using stadiometer and head length using spreading calliper in 200 medical undergraduatestudents (100 males and 100 females). Results: There is low statistically significant correlation betweenhead length and stature (r=0.25 for males and r=0.22 for females). Conclusion: Accurate stature estimationis not possible from percutaneous head length